Coping mechanisms to drug stock-outs among patients seeking mental healthcare at outpatient department in Butabika National Referral Mental Hospital, Uganda: A cross-sectional study - Angela Apio; Grifine Agarukamu; Gloria Nicole Amuron; Silas Ojuka; Mike Mugisha; Kalidi Rajab (PLoS ONE, 2026)
Background Mental disorders are responsible for a significant proportion of global health burden especially in developing countries. In sub-Saharan Africa optimum care for mental health patients is constrained by frequent drug stock-outs. Patients who are victims of drug stock-outs are compelled to seek coping mechanisms to this challenge. These coping mechanisms may either be adaptive or maladaptive. Consequently, persons living with mental illnesses are prone to experiencing undesirable outcomes. This study purposed to explore coping mechanisms to drug stock-outs among patients seeking care at an outpatient department (OPD) of a national mental healthcare facility in Kampala, Uganda. Methods This was an observational cross-sectional study. A sample size of 385 was obtained by systematic random sampling. Data was collected using a checklist and a questionnaire. The data was analyzed using SPSS version 29. Numerical variables were presented with means and standard deviations. Categorical variables were presented as frequencies and percentages. The results of the study were presented in tables, pie-charts and graphs. Results Less than half of the participants; 164/385(42.60%), had their prescriptions fully filled with an average prescription fulfillment rate of 66.36%. Majority of the patients were victims of drug stock-outs. The most popular coping mechanisms were; out-of-pocket purchase of prescribed drugs from pharmacies, patients returning to hospital on a later date, skipping drug doses and using unprescribed herbal remedies. The commonest undesirable outcomes of coping mechanisms were; worsening of symptoms, insomnia and relapse of signs and symptoms. Conclusion Drug stock-outs could have been responsible for low prescription fulfillment rates. This most likely prompted numerous patients to resort to alternative treatment modalities. These unprescribed treatment modalities could jeopardize patient prognosis and overall safety.